Pemanfaatan Limbah Tambak Garam Sebagai Koagulan Bittern Untuk Menurunkan Parameter Kekeruhan Pada Limbah Tahu - Pedro Caesariano; Muhammad Abdus Salam Jawwad (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The tofu industry produces wastewater with high turbidity, requiring treatment before being discharged into the environment. This study aims to utilize bittern, a byproduct of salt pond production, as an environmentally friendly alternative coagulant to reduce turbidity in tofu wastewater. Bittern was activated using three types of strong bases Ca(OH)₂, KOH, and NaOH with dosage variations of 40,50,60 mL and concentrations of 4%,6%,8%. The results showed that all activators enhanced the coagulation performance of bittern, with varying effectiveness under each treatment. NaOH provided the best result at a dosage of 50 mL and a concentration of 4%, achieving a turbidity removal efficiency of 95%. KOH reached optimal performance at 50 mL and 6%, with a turbidity removal efficiency of 93%, while Ca(OH)₂ achieved 85% efficiency at 50 mL and 6%. Overall, this study demonstrates that NaOH-activated bittern is an effective alternative coagulant with potential for sustainable application in tofu wastewater treatment.